1987
DOI: 10.1128/jb.169.9.3904-3909.1987
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determination and comparison of the exfoliative toxin A and toxin B genes from Staphylococcus aureus

Abstract: The DNA encoding the exfoliative toxin A gene (eta) of Staphylococcus aureus was cloned into bacteriophage Xgtll and subsequently into plasmid pLI50 on a 1,391-base-pair DNA fragment of the chromosome. Exfoliative toxin A is expressed in the Escherichia coli genetic background, is similar in length to the toxin purified from culture medium, and is biologically active in an animal assay. The nucleotide sequence of the DNA fragment containing the gene was determined. The protein deduced from the nucleotide seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 31 publications
2
89
0
2
Order By: Relevance
“…Sequences of the primers used as shown in Table 1 have been published by other authors [19][20][21][22][23] . The 25-μl reaction mix contained 5 μl of 10x reaction buffer (100 mM of TrisHCl, pH 8.8, 500 mM of KCl, 1 % Triton X-100, 15 mM of MgCl 2 ) 0.4 μl of dNTPs (10 mM); 50 pmol of primers, 2.5 U of Taq polymerase, 2.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Sequences of the primers used as shown in Table 1 have been published by other authors [19][20][21][22][23] . The 25-μl reaction mix contained 5 μl of 10x reaction buffer (100 mM of TrisHCl, pH 8.8, 500 mM of KCl, 1 % Triton X-100, 15 mM of MgCl 2 ) 0.4 μl of dNTPs (10 mM); 50 pmol of primers, 2.5 U of Taq polymerase, 2.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Staphylococcal scalded skin syndrome is caused by infection with Staphylococcus aureus strains that produce exfoliative toxin ETA, ETB, or both (14). The exfoliative toxins from S. aureus, ETA and ETB, have been cloned and their nucleotide sequences have been determined (12,17,20,22). Investigations have shown that the gene encoding ETA is located on the chromosome of S. aureus, while the gene encoding ETB is located on a 42-kb plasmid (reviwed by Arbuthnott [7]).…”
mentioning
confidence: 99%
“…The first group of exoproteins are alpha-toxin (14), beta-hemolysin (47), gammahemolysin (46), delta-hemolysin (20), and phospholipase C (9). The second group are toxic shock syndrome toxin-1 (TSST-1) (29), enterotoxins (3,4,8,15,22,52), protein A (34), and others (6,31,32,50,53), and the third group contains clumping factor (37) and others (7,12,23,45). More than 30 of these exoproteins that are significantly linked to pathogenesis have been purified to homogeneity, and the genes encoding these exoproteins have been cloned and sequenced (5,48 Abstract: We applied two-dimensional gel electrophoresis (2-DE) to the total exoproteins secreted from pathogenic MRSA strains and identified major protein spots by N-terminal amino acid sequence analysis.…”
mentioning
confidence: 99%